2020
DOI: 10.1016/j.ejor.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The median routing problem for simultaneous planning of emergency response and non-emergency jobs

Abstract: a b s t r a c tThis paper studies a setting in emergency logistics where emergency responders must also perform a set of known, non-emergency jobs in the network when there are no active emergencies going on. These jobs typically have a preventive function, and allow the responders to use their idle time much more productively than in the current standard. When an emergency occurs, the nearest responder must abandon whatever job he or she is doing and go to the emergency. This leads to the optimisation problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Our research builds directly on the work by Huizing et al on the MRP (Huizing et al, 2020) and the proposed MDSA-heuristic for solving the MRP. This problem has similarities to both the p-Median Problem and the Distance-Constrained Vehicle Routing Problem.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Our research builds directly on the work by Huizing et al on the MRP (Huizing et al, 2020) and the proposed MDSA-heuristic for solving the MRP. This problem has similarities to both the p-Median Problem and the Distance-Constrained Vehicle Routing Problem.…”
Section: Related Literaturementioning
confidence: 99%
“…Therefore, a fast heuristic is needed that provides good solutions within a few minutes. In Huizing et al (2020), MDSA was found to be the most effective heuristic for MRP. Roughly, MDSA consists of four steps, which are outlined below for later reference.…”
Section: An Mdsa-inspired Heuristicmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) proposed a multi-compartment vehicle routing model to solve the cold-chain distribution problem. Huizing et al. (2020) studied the emergency logistics with non-emergency jobs, and formulated it as a median routing problem to minimize the expected response time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the agents might correspond to an 'emergency fleet' (e.g., police patrol force, emergency medical coverages, railway emergency responders) that one needs to schedule to provide a good emergency response time over a pre-specified time horizon. In fact, we arrived at the Traveling k-Median Problem introduced in this paper through our (more applied) investigations in the domain of emergency logistics; more specifically, the Traveling k-Median Problem considered here is a stylized variant of the so-called Median Routing Problem studied in [12].…”
Section: Introductionmentioning
confidence: 99%